Reliability and Validity Measures of the Patellofemoral Subscale KOOS-PF in Greek Patients with Patellofemoral Pain - Ioannis Moros; Eleni C. Boutsikari; George Plakoutsis; Elefterios Paraskevopoulos; George A. Koumantakis; Maria Papandreou (Journal of Functional Morphology and Kinesiology)
Background: Patellofemoral pain (PFP) is one of the most common multifactorial musculoskeletal pathologies affecting the knee joint. The prevalence of PFP in the general population ranges from 11% to 17%, with higher rates observed in specific groups such as females, runners, military personnel, and young athletes. To assess symptoms associated with PFP, the patellofemoral subscale (KOOS-PF) was developed, consisting of 11 questions that evaluate pain, stiffness, and quality of life. The KOOS-PF scale has already been validated and shown to be reliable in both its Spanish and Arabic versions. Objectives: The aim of this study was to assess the reliability and validity of the KOOS-PF scale in the Greek language among the Greek population with patellofemoral pain. Methods: Fifty-five participants aged 18–65 years who suffered from PFP were evaluated in two phases on the first and third days to determine the reliability and validity of the measures of KOOS-PF in the Greek language. Construct validity was assessed using the knee outcome survey scale—activities of daily living scale (KOS-ADLS). Reliability was measured through repeated measurements (test–retest) using intraclass coefficient correlation (ICC), standard error of measurement (SEM), and smallest detectable difference (SDD). Internal consistency was evaluated using Cronbach’s coefficient a. The significance level was set at 5% (α = 0.05). Results: The KOOS-PF measures showed high internal consistency reliability (Cronbach’s alpha 0.87, p = 0.05) and high test–retest reliability (ICC = 0.95, p = 0.05, SEM = 3.7, SDC = 13.57). Additionally, the Greek version of the KOOS-PF exhibited high construct validity when correlated with the KOS-ADLS scale (r = 0.72, p = 0.001). Conclusions: The KOOS-PF scale displayed high reliability and construct validity for measuring patellofemoral pain in the Greek population.